Considering cross-cultural differences in sleep duration between Japanese and Canadian university students - Cheung, Benjamin Y.; Takemura, Kosuke; Ou, Christine; Gale, Anne; Heine, Steven J. (PloS one, 2021)
Sleep is a fundamental biological process that all humans exhibit, and there is much evidence that people suffer adverse health outcomes from insufficient sleep. Despite this evidence, much research demonstrates significant heterogeneity in the amounts that people sleep across cultures. This suggests that despite serving fundamental biological functions, sleep is also subject to cultural influence. Using self-report and actigraphy data we examined sleep among European Canadian, Asian Canadian, and Japanese university students. Significant cultural differences emerged in terms of various parameters of sleep (e.g. sleep time), and beliefs about sleep (e.g. perceived relation between sleep and health). Despite sleeping significantly less than European Canadians, Japanese participants slept less efficiently, yet reported being less tired and having better health. Moreover, relative to European Canadians, Japanese participants perceived a weaker relation between sleep and physical health, and had a significantly shorter ideal amount of sleep. Asian Canadians’ sleep behaviors and attitudes were largely similar to European Canadians suggesting that people acculturate to local cultural sleep norms.